The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.04.19.20071647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review of COVID-19 autopsies: accelerated hyaluronan concentration as the primary driver of morbidity and mortality in high-risk COVID-19 patients: with therapeutic introduction of an oral hyaluronan inhibitor in the prevention of “Induced Hyaluronan Storm” Syndrome

Abstract: Background To date, more than 161,000 people have died from the coronavirus disease 2019 (COVID-19) yet the fundamental drivers of the morbidity and mortality remain uncertain. Clinicians worldwide appear to be at a loss to know how to prevent and treat the severe respiratory distress in these patients effectively. Consequently, the fundamental mechanisms leading to death in high-risk patients with COVID-19 need to be discovered and addressed with urgency. Despite a marked drop in frequency, the post-mortem au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, in another autopsy study of a COVID-19 patient, histological analysis found extensive hyaline membranes, which the authors interpreted as indicative of ARDS ( Xu et al, 2020 ). Finally, a meta-analysis showed that there was a statistically significant 4.6 fold difference in lung weight of COVID-19 patients versus controls, which they conclude is consistent with the HA-hydrogel formation known to occur in ARDS ( Mong et al, 2020 ).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, in another autopsy study of a COVID-19 patient, histological analysis found extensive hyaline membranes, which the authors interpreted as indicative of ARDS ( Xu et al, 2020 ). Finally, a meta-analysis showed that there was a statistically significant 4.6 fold difference in lung weight of COVID-19 patients versus controls, which they conclude is consistent with the HA-hydrogel formation known to occur in ARDS ( Mong et al, 2020 ).…”
Section: Resultssupporting
confidence: 66%
“…Reports from blood studies include leukopenia, eosinopenia, neutrophilia, elevated liver enzymes, C-reactive protein, and ferritin ( Fan et al, 2020 ; Huang et al, 2020 ; Goyal et al, 2020 ). Furthermore, autopsies have reported extensive hyaline membrane formation in the lungs of COVID-19 patients ( Barton et al, 2020 ; Xu et al, 2020 ; Adachi et al, 2020 ; Mong et al, 2020 ). Specifically, histological analysis of the lungs of a deceased COVID-19 patient showed organizing hyaline membranes in the early stages of alveolar lesions and prominent hyaline membranes in the exudative phase of diffuse alveolar damage ( Adachi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, as detailed below, STAT3 indirectly activates TGF-β in the extracellular matrix (ECM), and TGF-β upregulates PAI-1 production [93]. Fifth, severe ARDS cases of COVID-19 result in diffuse alveolar damage (DAD) and the formation of hyaline membranes [94]. Hyaluronan (HA) is essential for many biological functions, but it is a causative agent in ARDS when it becomes a low-molecular-weight HA (LMW-HA) [95].…”
Section: Stat3 and Coagulopathymentioning
confidence: 99%
“…24 The alveolar cavity is often filled with serum, fibrin exudate and extensive transparent hyaline membrane formations, as observed in autopsies. 22,[25][26][27] White blood cells that infiltrate the alveoli are mainly monocytes and macrophages. Type II lung alveolar cell proliferation and focal lung cell shedding can be observed.…”
Section: Pathological Anatomymentioning
confidence: 99%